Temporary implants and particulate dentin graft protecting traditional implants in severe periodontal patient: A case report - José Luis Calvo-Guirado (Wolters Kluwer Medknow Publications, 2021)
Provisional implants (PIs) can offer a total contribution to a patient's esthetic comfort and chew during the integration of standard implants. Although temporary implants are not intended for osseointegration and have to withdraw at there or 4 months, most of them begin to move during this process, and most of them had extracted before standard implants integration. Resin fixed prosthesis attached to temporary implant abutments gives the patient stability, gives esthetics, and gives protection to traditional implants, compared to removable prostheses, which more quickly leads to the loosening and loss of these temporary implants. Temporary implants could be used with cemented or screwed resin prosthesis or with titanium framework, depending on the patient's bite, bruxism, or clenching. All PIs are made in one piece, titanium grade 5, with V threads and a Bioetched surface (rough surface) to increase the insertion torque and bone to implant contact in soft and hard bone. Temporary upper fixed denture, relined with resin, is the easiest solution for protecting and reducing the risk of failure of some of the standard implants. The possible solution in such cases is the use of temporary implants as support for the fixed structure, acting as protection of traditional implants and bone grafts. Our clinical case was made with six temporary implants TR® 2.7 mm diameter by 13 mm length, grinding extracted teeth using smart dentin grinder, and fixed temporary denture for 3 months. At 4 months, a complete zirconium denture was screwed in standard implants.